2018
DOI: 10.1192/bja.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes in depression: reducing drop-out rates in cognitive therapy

Abstract: SUMMARYAlthough cognitive therapy is a promising treatment for depression, high drop-out rates and, conversely, the specific elements that make the intervention effective continue to puzzle practising clinicians. This article discusses both therapistrelated factors (including competence and competencies) and patient-related factors (such as engagement in therapy and external logistical problems with attendance) that are related to drop-out and suggests practical ways to address them and improve outcomes. It ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…The therapists in our study discussed that some dropout from the treatment should be expected. This is in line with findings from previous studies where dropout rates on CBT were investigated (Swift and Greenberg, 2012;Fernandez et al, 2015;Pentaraki, 2018;Schmidt et al, 2019). Dropout from the treatment should be anticipated, but it should also be emphasized that this guided iCBT program has demonstrated to be effective, also for patients who did not complete all modules (Jakobsen et al, 2017;Nordgreen et al, 2019).…”
Section: Theme 1: For the Right Person At The Right Timesupporting
confidence: 88%
“…The therapists in our study discussed that some dropout from the treatment should be expected. This is in line with findings from previous studies where dropout rates on CBT were investigated (Swift and Greenberg, 2012;Fernandez et al, 2015;Pentaraki, 2018;Schmidt et al, 2019). Dropout from the treatment should be anticipated, but it should also be emphasized that this guided iCBT program has demonstrated to be effective, also for patients who did not complete all modules (Jakobsen et al, 2017;Nordgreen et al, 2019).…”
Section: Theme 1: For the Right Person At The Right Timesupporting
confidence: 88%
“…Future studies may mitigate the impact of testing by selecting fewer measures based on previous findings, focused on core cognitive domains that are expected to improve following GMT. Notably, the dropout rate in our study is consistent with high dropout rates found across psychological interventions for depression [51], where it is possible that the symptoms of depression (e.g., anhedonia, low motivation) may interfere with initiation or completion of treatment. A major limitation of the study is that it did not explore the interaction of cognition and emotion through assessment of emotional regulation among individuals with MDD and the use of cognitive tasks that may be perturbed by emotion (e.g., the emotional Stroop).…”
Section: Discussionsupporting
confidence: 84%
“…We acknowledge that undertaking a self-directed CBT program may not be of interest to all patients with needle fear. Based on previous studies reporting on the use of CBT interventions, dropout rates for psychotherapy range from 16% at the pretreatment phase to 26% at the treatment phase, with some studies reporting an average dropout rate of 47% [ 35 , 36 ]. Acceptability will be assessed qualitatively, and we anticipate that the intervention will be acceptable from our qualitative approaches.…”
Section: Methodsmentioning
confidence: 99%